Dispersing and softening agent for positive electrode slurry of lithium battery as well as preparation method and application of dispersing and softening agent

By using a dispersion softener prepared by block comb copolymer and polyurethane copolymer in the positive electrode slurry of lithium battery, the problem of insufficient dispersion and flexibility under high solids content is solved, efficient dispersion and softening effects are achieved, and the capacity and processing efficiency of lithium batteries are improved.

CN119905587APending Publication Date: 2025-04-29ANHUI PULITONG NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411872543.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

After increasing the solid content of the positive electrode slurry of lithium battery, the dispersion is poor, and the flexibleness of the electrode sheet is not good during the thick coating and fast coating process, which is prone to cracking, affecting the quality and life of the electrode sheet.

Method used

The dispersion softening agent prepared by block copolymer and polyurethane copolymer is prepared by random radical solution copolymer, and the polyurethane copolymer is prepared by solution polymerization and chain extension reaction. Combined with steric hindrance, it achieves excellent dispersion and softening effect on the powder in the positive electrode slurry.

Benefits of technology

With an addition amount of no more than 0.5%, the solid content and dispersion of the positive electrode slurry are significantly improved, the flexibility and compaction density of the electrode sheet are improved, the risk of belt breakage is reduced, and the capacity and processing efficiency of lithium batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005196103070000051
    Figure BDA0005196103070000051
  • Figure BDA0005196103070000061
    Figure BDA0005196103070000061
  • Figure BDA0005196103070000081
    Figure BDA0005196103070000081
Patent Text Reader

Abstract

The invention relates to the technical field of H01M4 / 62, in particular to a dispersing and softening agent for lithium battery positive electrode slurry and a preparation method and application thereof.The dispersing and softening agent at least comprises, by mass, 10-90% of block comb-type copolymer and the balance polyurethane copolymer, and the dispersing and softening agent can be used for dispersing and softening lithium battery positive electrode slurry on the premise that the addition amount does not exceed 0.5%. And meanwhile, the problems that the dispersity is poor after the solid content is increased and the flexibility of the pole piece is poor in the thick coating and fast coating processes are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the H01M4 / 62 technical field, and in particular to a dispersing softener for lithium battery positive electrode slurry, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices, drones, power tools, electric vehicles and other fields due to their high voltage, high specific energy, long cycle life, good safety performance and low self-discharge. The "Guiding Opinions on Promoting the High-Quality Development of Light Industry" proposed that high-efficiency lithium battery safety technology is one of the key R&D breakthrough technologies, requiring lithium batteries to have higher capacity and higher processing efficiency, so it is necessary to increase the coating thickness and coating speed of the pole piece. In the actual operation process, the thick coating of the pole piece requires an increase in the solid content of the slurry. While increasing the solid content, it is also necessary to evenly disperse solid particles, adhesives and other materials, that is, to improve the dispersibility of the slurry. The pole piece is prone to cracking during the drying process when the coating speed is accelerated. Therefore, it is necessary to increase the flexibility of the pole piece. After the pole piece is dried, the cold pressing pressure of the thick pole piece will also increase, and the ductility of the pole piece also needs to be enhanced. In addition, during the thick coating and fast coating process, conductive agents, adhesives, etc. will float up, which will also affect the flexibility of the pole piece, worsen the brittleness of the pole piece, and increase the risk of light leakage during winding, hot pressing and folding of the pole piece.

[0003] In view of the above problems, the current solution in the industry is to add dispersants and softeners to the slurry. For example, a Chinese patent (publication number CN 115863643 A) discloses a dispersant and softener for lithium-ion battery positive electrode slurry and its application. By introducing the dispersant and softener into the positive electrode slurry of lithium-ion batteries, the fluidity problem of the slurry can be solved to a certain extent, but the problem of the flexibility of the pole piece cannot be effectively solved. In addition, the addition ratio of additives in the positive electrode slurry is very limited, generally not exceeding 0.5%. If it is higher, the capacity of the lithium battery will be reduced. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a dispersing softener for lithium battery positive electrode slurry, which can solve the problems of poor dispersibility after increasing the solid content and poor flexibility of the electrode during thick coating and fast coating at the same time, under the premise of not exceeding 0.5% of the added amount.

[0005] On one hand, the present invention provides a dispersing softener for lithium battery positive electrode slurry, which comprises at least the following components by mass percentage: 10-90% of a block comb copolymer and the balance of a polyurethane copolymer.

[0006] As a preferred technical solution, the block comb copolymer has a structural formula shown in formula (1),

[0007] Formula (1): Wherein, a, b, c are natural numbers, but not 0 at the same time; R1 is H or COOH, R2 is H or CH3, R3 is a single-terminal amino polyether group, R4 is a phenyl, pyridine or pyrrolidone group, R5 is H or CH3, and R6 is H or CH2H3PO4.

[0008] As a preferred technical solution, the polyurethane copolymer has a structural formula shown in formula (2),

[0009] Formula (2): Wherein, R1 represents an isocyanate group with NCO, R2 represents an aliphatic polyether, and n is a non-zero natural number.

[0010] As a preferred technical solution, the block comb copolymer includes at least the following raw materials by weight: 90-120 parts of single-terminal amino polyether, 5-10 parts of acid anhydride, 0.01-0.1 parts of inhibitor, 10-20 parts of vinyl monomer, 0-100 parts of solvent, and 0.1-0.3 parts of initiator.

[0011] As a preferred technical solution, the single-ended amino polyether is selected from at least one of polyetheramine 2070, polyetheramine M1000, and polyetheramine FL-1000, preferably polyetheramine 2070.

[0012] As a preferred technical solution, the acid anhydride is an acid anhydride containing vinyl group.

[0013] Preferably, the vinyl-containing acid anhydride is selected from at least one of methacrylic anhydride, acrylic anhydride and maleic anhydride, preferably maleic anhydride (maleic anhydride).

[0014] As a preferred technical solution, the inhibitor is p-hydroxyanisole.

[0015] As a preferred technical solution, the solvent is selected from at least one of methanol, isopropanol, N-methylpyrrolidone, N-dimethylformamide, and dimethyl sulfoxide, preferably N-methylpyrrolidone.

[0016] As a preferred technical solution, the vinyl monomer at least includes a vinyl monomer containing an acidic group.

[0017] Preferably, the vinyl monomer containing an acidic group is selected from at least one of acrylic acid, methacrylic acid, and 2-hydroxyethyl methacrylate phosphate, preferably 2-hydroxyethyl methacrylate phosphate.

[0018] As a preferred technical solution, the vinyl monomer further includes at least one of styrene, vinyl pyridine and N-vinyl pyrrolidone.

[0019] As a preferred technical solution, the mass ratio of the vinyl monomer containing an acidic group to styrene, vinyl pyridine or N-vinyl pyrrolidone is (10-15):(3-6).

[0020] As a preferred technical solution, the initiator is an azo initiator or a peroxide compound initiator.

[0021] Preferably, the peroxide compound initiator is selected from any one of benzoyl peroxide, dodecyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, cumene hydroperoxide, tert-butyl hydroperoxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, and di-tert-amyl peroxide.

[0022] Preferably, the azo initiator is selected from any one of azobisisobutyronitrile and azobisisoheptanenitrile.

[0023] As a preferred technical solution, the preparation method of the block comb-type copolymer is as follows: after adding the single-ended amino polyether and the inhibitor into a reaction container and stirring and mixing, acid anhydride is added dropwise at 15-30°C with stirring, and the temperature is kept not more than 100°C. After the addition is completed, the reaction is continued at 90-110°C for 0.5-1.5h to obtain a single-ended vinyl polyether monomer; the vinyl monomer and the initiator are dissolved in a solvent, added to the single-ended vinyl polyether monomer, and the reaction is continued at 90-110°C for 1-3h to obtain the block comb-type copolymer.

[0024] As a preferred technical solution, the raw materials for preparing the polyurethane copolymer include at least 20-200 parts of polyether monomer, 15-40 parts of isocyanate, 0.01-0.3 parts of catalyst, 1-10 parts of chain extender, and 0-200 parts of organic solvent, by weight.

[0025] As a preferred technical solution, the polyether monomer is a polyether monomer having double terminal hydroxyl groups.

[0026] Preferably, the polyether monomer having double-terminal hydroxyl groups is selected from at least one of PEG200, PEG400, PEG800, PEG2000, PEG4000, PPG800, PPG2000, and PPG4000, preferably PEG200.

[0027] As a preferred technical solution, the catalyst is selected from at least one of triethanolamine, N,N-dimethylethanolamine, N,N-dimethylcyclohexylamine, bis(2-dimethylaminoethyl) ether, N,N,N,N-tetramethylalkylenediamine, triethylamine, N,N-dimethylbenzylamine, and dibutyltin dilaurate, preferably dibutyltin dilaurate.

[0028] As a preferred technical solution, the chain extender is selected from at least one of 3,3'-dichloro-4,4'-diaminophenylmethane (MOCA), diethyltoluenediamine (DETDA), di-sec-butylaminodiphenylmethane (MDBA), dimethylolpropionic acid (DMPA), dimethylolbutanoic acid (DMBA) and 1,4-butanediol (BDO), preferably 1,4-butanediol (BDO).

[0029] As a preferred technical solution, the organic solvent is selected from at least one of methanol, isopropanol, N-methylpyrrolidone, N-dimethylformamide, and dimethyl sulfoxide, preferably N-methylpyrrolidone (NMP).

[0030] As a preferred technical solution, the preparation method of the polyurethane copolymer is as follows: adding a polyether monomer to a container equipped with a stirring device and a vacuum device, heating to 100-150°C, maintaining the vacuum degree below 0.09MPa, and removing water in vacuum for 1-3h; cooling, adding an organic solvent and stirring to dissolve for 20-40min, adding isocyanate and a catalyst dropwise, heating to 60-80°C, introducing N2, reacting for 1.5-3h, adding a chain extender and continuing the reaction for 1.5-3h to obtain a polyurethane copolymer.

[0031] The present invention adopts the dispersing softener prepared by the block comb copolymer and the polyurethane copolymer to prepare the positive electrode slurry with high solid content and low viscosity, and can use relatively less solvent to achieve uniform dispersion of the positive electrode slurry, effectively saving the time of the production process, improving production efficiency, and improving the flexibility of the pole piece, reducing the risk of breaking the band, and increasing the compaction density of the pole piece. Specifically, the present invention adopts single-terminal amino polyether, vinyl-containing acid anhydride, vinyl monomer containing acidic group and other vinyl monomers under the action of peroxide or azo initiator, and prepares the block comb copolymer shown in formula (1) by random free radical solution copolymerization, so that the provided dispersing softener can be well adsorbed on the surface of lithium iron phosphate and conductive agent material, and cooperates with steric hindrance to achieve excellent dispersion of powder in the positive electrode slurry. Furthermore, by using a polyether monomer with a double-terminal hydroxyl group, an isocyanate with a free NCO group and a chain extender under the action of a catalyst, a solution polymerization is carried out and then a chain extender is added to extend the chain to prepare a polyurethane copolymer represented by formula (2), thereby further improving the dispersibility of the positive electrode slurry system and improving the flexibility of the subsequent electrode sheet.

[0032] Another aspect of the present invention provides a method for preparing a dispersing softener for lithium battery positive electrode slurry, which comprises at least the following steps: mixing a block comb copolymer and a polyurethane copolymer to obtain the dispersing softener.

[0033] A third aspect of the present invention provides a positive electrode slurry for a lithium ion battery, wherein the amount of a dispersing softener added to the positive electrode slurry for a lithium ion battery is less than 0.5 wt %.

[0034] As a preferred technical solution, the solid content of the lithium-ion battery positive electrode slurry is 55-60wt%, and the solid component contains 95.7wt% lithium iron phosphate, 0.3wt% dispersing softener, 2wt% conductive carbon black, and 2wt% adhesive PVDF.

[0035] As a preferred technical solution, the preparation method of the lithium-ion battery positive electrode slurry is: dissolve 12g of binder PVDF in 400g of N-methylpyrrolidone solvent to prepare a solution, add 576g of lithium iron phosphate, 12g of conductive carbon black and 1.725g of dispersing softener in sequence, rotate at 1500r / min, and stir for 60min to obtain the lithium-ion battery positive electrode slurry.

[0036] Beneficial Effects

[0037] 1. The present invention provides a dispersing and softening agent for lithium battery positive electrode slurry, which can solve the problems of poor dispersibility after increasing the solid content and poor flexibility of the electrode during thick coating and fast coating at the same time under the premise of not more than 0.5% of the added amount.

[0038] 2. The dispersing softener prepared by the block comb copolymer and the polyurethane copolymer of the present invention can prepare a positive electrode slurry with a higher solid content and a lower viscosity, and can use relatively less solvent to achieve uniform dispersion of the positive electrode slurry, effectively saving time in the production process and improving production efficiency. It can also improve the flexibility of the electrode, reduce the risk of band breakage, and increase the compaction density of the electrode.

[0039] 3. The present invention adopts single-terminal amino polyether, vinyl-containing acid anhydride, vinyl monomer containing acidic group and other vinyl monomers under the action of peroxide or azo initiator, and prepares the block comb copolymer shown in formula (1) by random radical solution copolymerization, so that the provided dispersing softener can be well adsorbed on the surface of lithium iron phosphate and conductive agent material, and the excellent dispersion effect on the powder in the positive electrode slurry is achieved by the steric hindrance.

[0040] 4. The present invention prepares the polyurethane copolymer represented by formula (2) by using a polyether monomer having a double-terminal hydroxyl group, an isocyanate having a free NCO group and a chain extender under the action of a catalyst, through solution polymerization and then adding a chain extender for chain extension, thereby further improving the dispersibility of the positive electrode slurry system and improving the flexibility of the subsequent electrode sheet.

[0041] 5. The dispersing and softening agent provided by the present invention can play a good dispersing and softening and toughening role in lithium (manganese) iron phosphate slurry when used in a lower addition amount, meeting the actual use requirements of the pole piece quality under high coating thickness and coating speed, and providing a possibility for lithium batteries to have higher capacity and higher processing efficiency. DETAILED DESCRIPTION

[0042] Examples 1-18

[0043] Embodiments 1-18 of the present invention provide a dispersing softener for lithium battery positive electrode slurry, and the formula is shown in Table 1 in terms of mass percentage.

[0044] Table 1

[0045]

[0046]

[0047] In Table 1:

[0048] The block comb copolymer 1 is a single-end vinyl polyether monomer, and the preparation method is as follows: 106.5g of single-end amino polyether M2070 and 0.07g of inhibitor p-hydroxyanisole are added to a reaction container and stirred and mixed, and then 7.7g of maleic anhydride is added dropwise at 25°C with stirring, and the temperature is kept not higher than 100°C. After the addition is completed, the reaction is continued at 100°C for 1h to obtain a single-end vinyl polyether monomer.

[0049] The preparation method of the block comb-type copolymer 2 is as follows: 106.5g of the single-end amino polyether M2070 and 0.07g of the inhibitor p-hydroxyanisole are added to a reaction container and stirred and mixed, and then 7.7g of maleic anhydride is added dropwise at 25°C with stirring, and the temperature is kept not higher than 100°C. After the addition is completed, the reaction is continued at 100°C for 1h to obtain a single-end vinyl polyether monomer; 11.4g of the vinyl monomer 2-hydroxyethyl methacrylate phosphate and 0.2g of the initiator azobisisobutyronitrile are dissolved in 100g of the solvent NMP, added to the single-end vinyl polyether monomer, and the reaction is continued at 100°C for 2h to obtain the block comb-type copolymer 2.

[0050] The preparation method of the block comb-type copolymer 3 is as follows: 106.5g of the single-end amino polyether M2070 and 0.07g of the inhibitor p-hydroxyanisole are added to a reaction container and stirred and mixed, and then 7.7g of maleic anhydride is added dropwise at 25°C with stirring, and the temperature is kept not higher than 100°C. After the addition is completed, the reaction is continued at 100°C for 1h to obtain a single-end vinyl polyether monomer; 11.4g of the vinyl monomer 2-hydroxyethyl methacrylate phosphate, 5.2g of the vinyl monomer styrene and 0.2g of the initiator azobisisobutyronitrile are dissolved in 100g of the solvent NMP, added to the single-end vinyl polyether monomer, and the reaction is continued at 100°C for 2h to obtain the block comb-type copolymer 3.

[0051] The preparation method of polyurethane copolymer 1 is as follows: 200g of polyether monomer PEG2000 is added to a container equipped with a stirring device and a vacuum device, heated to 120°C, the vacuum degree is maintained below 0.09MPa, and water is removed under vacuum for 2h; the temperature is lowered to 25°C, 200g of organic solvent NMP is added, stirred and dissolved for 30min, 25g of toluene diisocyanate and 0.1g of catalyst dibutyltin dilaurate are added dropwise, the temperature is raised to 70°C, N2 is introduced, the reaction is carried out for 2h, 5g of chain extender 1,4-butanediol is added, and the reaction is continued for 2h to obtain polyurethane copolymer 1.

[0052] The preparation method of polyurethane copolymer 2 is as follows: add 200g of polyether monomer PEG2000 into a container equipped with a stirring device and a vacuum device, heat to 120°C, maintain the vacuum degree below 0.09MPa, and remove water in vacuum for 2h; cool to 25°C, add 200g of organic solvent NMP and stir to dissolve for 30min, dropwise add 25g of MDI and 0.1g of catalyst dibutyltin dilaurate, heat to 70°C, introduce N2, react for 2h, add 5g of chain extender 1,4-butanediol and continue to react for 2h to obtain polyurethane copolymer 2.

[0053] The preparation method of polyurethane copolymer 3 is as follows: 20g of polyether monomer PEG200 is added to a container equipped with a stirring device and a vacuum device, heated to 120°C, the vacuum degree is maintained below 0.09MPa, and vacuum dehydration is performed for 2h; the temperature is lowered to 25°C, 20g of organic solvent NMP is added, stirred and dissolved for 30min, 25g of hexamethylene diisocyanate and 0.1g of catalyst dibutyltin dilaurate are added dropwise, the temperature is raised to 70°C, N2 is introduced, the reaction is performed for 2h, 5g of chain extender 1,4-butanediol is added, and the reaction is continued for 2h to obtain polyurethane copolymer 3.

[0054] On the other hand, Examples 1-18 of the present invention provide a method for preparing a dispersing softener for lithium battery positive electrode slurry, comprising the following steps: stirring and mixing a block comb copolymer and a polyurethane copolymer to obtain the obtained product.

[0055] Application Examples 1-18

[0056] Application Examples 1-18 of the present invention provide a positive electrode slurry for a lithium-ion battery. The preparation method of the positive electrode slurry for a lithium-ion battery is as follows: 12 g of a binder PVDF is dissolved in 400 g of an N-methylpyrrolidone solvent to prepare a solution, and 576 g of lithium iron phosphate, 12 g of a conductive carbon black and 1.725 g of a dispersing softener (Example 1-18) are added in sequence, the rotation speed is 1500 r / min, and the mixture is stirred for 60 min to obtain the positive electrode slurry 1-18 for a lithium-ion battery.

[0057] Performance Testing

[0058] 1. The positive electrode slurry of the lithium ion battery without adding the dispersing softener is used as a blank sample (others are the same as those in Application Example 1-18). The positive electrode slurry 1-18 of the lithium ion battery provided in Application Example 1-18 and the blank sample are kept at a constant temperature of 25°C in a constant temperature box for 2 hours, and the viscosity of the material is tested using a NDJ5S digital rotational viscometer; then the material is kept at a constant temperature of 25°C in a constant temperature box for 24 hours and the viscosity of the material is tested again using a NDJ5S digital rotational viscometer. The test results are shown in Table 2.

[0059] 2. The positive electrode slurry of the lithium ion battery without adding the dispersing softener was used as a blank sample (other conditions were the same as those in Application Example 1-18). The positive electrode slurry 1-18 of the lithium ion battery provided in Application Example 1-18 and the blank sample were roller-coated to prepare the positive electrode sheet. The coating surface density was 17.11 g / cm 3 By adjusting the thickness after rolling, the compaction density reaches 2.4g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 , cut the electrode into a 10cm*10cm square electrode, and then place it on the softness tester. By applying pressure to the electrode, the electrode will apply a reaction force to the softness tester. The pressure curve is displayed by the built-in sensor of the tester. The highest point of the curve is the softness of the electrode. The larger the value, the harder the electrode, and vice versa. The test results are shown in Table 2.

[0060] Table 2

[0061]

Claims

1. A dispersing softener for lithium battery positive electrode slurry, characterized in that: Calculated by mass percentage, it at least comprises the following components: 10-90% of the block comb copolymer and the balance of the polyurethane copolymer.

2. The dispersing softener for lithium battery positive electrode slurry according to claim 1, characterized in that: The block comb copolymer has a structural formula shown in formula (1), Formula (1): Wherein, a, b, c are natural numbers but are not 0 at the same time; R1 is H or COOH, R2 is H or CH3, R3 is a single-terminal amino polyether group, R4 is a phenyl group, a pyridine group or a pyrrolidone group, R5 is H or CH3, and R6 is H or CH2H3PO4.

3. The dispersing softener for lithium battery positive electrode slurry according to claim 2, characterized in that: The polyurethane copolymer has the structural formula shown in formula (2), Formula (2): Wherein, R1 represents an isocyanate group with NCO, R2 represents an aliphatic polyether, and n is a non-zero natural number.

4. The dispersing softener for lithium battery positive electrode slurry according to claim 3, characterized in that: The block comb copolymer comprises at least the following raw materials by weight: 90-120 parts of single-terminal amino polyether, 5-10 parts of acid anhydride, 0.01-0.1 parts of polymerization inhibitor, 10-20 parts of vinyl monomer, 0-100 parts of solvent, and 0.1-0.3 parts of initiator.

5. The dispersing and softening agent for lithium battery positive electrode slurry according to claim 4, characterized in that: The acid anhydride is an acid anhydride containing a vinyl group.

6. The dispersing and softening agent for lithium battery positive electrode slurry according to claim 5, characterized in that: The vinyl monomer includes at least a vinyl monomer containing an acidic group.

7. The dispersing and softening agent for lithium battery positive electrode slurry according to claim 6, characterized in that: The vinyl monomer further comprises at least one of styrene, vinyl pyridine and N-vinyl pyrrolidone.

8. The dispersing and softening agent for lithium battery positive electrode slurry according to claim 7, characterized in that: The raw materials for preparing the polyurethane copolymer include at least 20-200 parts of polyether monomer, 15-40 parts of isocyanate, 0.01-0.3 parts of catalyst, 1-10 parts of chain extender and 0-200 parts of organic solvent in parts by weight.

9. A method for preparing a dispersing softener for lithium battery positive electrode slurry according to any one of claims 1 to 8, characterized in that: The method at least comprises the following steps: mixing the segmented comb-type copolymer and the polyurethane copolymer to obtain the product.

10. A lithium ion battery positive electrode slurry containing the dispersing softener for lithium battery positive electrode slurry according to any one of claims 1 to 8, characterized in that: The amount of the dispersing and softening agent added to the lithium ion battery positive electrode slurry is less than 0.5 wt %.

Citation Information

Patent Citations

  • Dispersing and softening agent for positive electrode slurry of lithium ion battery and application of dispersing and softening agent

    CN115863643A

Cited By

  • Softening agent for positive pole piece of lithium ion battery as well as preparation method and application of softening agent

    CN121591990A

  • Positive electrode softening agent, softening agent solution, positive electrode plate and battery

    CN121699101A